A pilot study on the differential urine proteomic profile of subjects with community-acquired acute kidney injury who recover versus those who do not recover completely at 4 months after hospital discharge - Kaur, Harpreet; Kamboj, Kajal; Naik, Sachin; Kumar, Vivek; Yadav, Ashok Kumar (Frontiers in Medicine, 2024)
Community acquiredacute kidney injury (CA-AKI) is a sudden structural damage and loss of kidney function in otherwise healthy individuals outside of hospital settings having high morbidity and mortality rates worldwide. Long-term sequelae of AKI involve an associated risk of progression to chronic kidney disease (CKD). Serum creatinine (SCr) the currently used clinical parameter for diagnosing AKI varies greatly with age, gender, diet and muscle mass.In the present study, we investigated the difference in urinary proteomic profile of subjects that recovered (R) and incompletely recovered (IR) from CA-AKI, 4 months after hospital discharge.Study subjects were recruited form ongoing study of CA-AKI cohort. Patients with either sex and age >18 years with no underline CKD were enrolled at the time of hospital discharge.Incomplete recovery from CA-AKI was defined as eGFR < 60 ml/min/1.73 m2 or dialysis dependence at 4 months after discharge. Second-morning urine samples were collected, and proteome analysis was performed with LC-MS/MS. Data was analyzed by Proteome Discoverer platform 2.2 (Thermo Scientific) using statistical and various bioinformatics tools for abundance of protein, cellular component, protein class and biological process were analyzed in recovered and incompletely recovered group.Total of 28 subjects (14 in each group) were enrolled. Collectively, 2019 peptides and proteins with 30 high abundance proteins in the incompletely recovered group (R/IR <0.5, abundance ratio adj. p-value <0.05) and 11 high abundance proteins in the incompletely recovered group (R/IR >2.0, abundance ratio adj. p-value <0.05) were identified. Tissue specificity analysis, GO enrichment analysis and pathway enrichment analysis revealed significant proteins in both the groups that are part of different pathways and might be playing crucial role in renal recovery during the four-month span after hospital discharge.In conclusion, this study helped in identifying potential proteins and associated pathways that are either upregulated or downregulated at the time of hospital discharge in incompletely recovered CA-AKI patients that can be further investigated to check for their exact role in the disease progression or repair.